المنهج الحركى في تفسير الشيخ سعيد حوى : دراسة تحليلية - Haziyah binti Hussin (Kulliyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2014)
The concept of manhaj haraki in tafsir and its methodological approaches remain relatively unclear and unknown; in fact few scholars discussed it. Thus, it is imperative to discover the characteristics and features of manhaj haraki by studying tafsir books which have been applied and adhered to this manhaj. Among these books are al-Asas fi al-Tafsir written by Sheikh Sa'id Hawwa, a renowned Muslim Brotherhood figure in Syria. The present research aims to uncover the concept of manhaj haraki in tafsir as well as introduce the book of al-Asas and exegetical methodology of Sheikh in it. Also, it deduces the methodological approach of manhaj haraki in this book and identifies factors that influence and lead to the creation of this manhaj. The researcher combined library research and field research, which among others involved conducting interviews with individuals who are closely related to Hawwa. The methodological approach of tafsir haraki has been identified by using the inductive method, while descriptive analytical method was conducted to uncover the concept of manhaj haraki in tafsir, and to describe the relationship between various phenomena and Hawwa's tafsir approach. The study demonstrates manhaj haraki is a specific practical outline that was influenced by the Prophet, his companions, and the pious predecessors, that is used to uncover the meanings of the Quran, to make people understand, and to enlighten people with an approach to the Quran that is both functional and realistic. The methods and characteristics of tafsir haraki as evident in al-Asas are; comprehensive and overall view of the Quran, emphasis on the basic objectives of the Quran, emphasis on the practical application of the Quran in reality and life, simplifying issues or staying away from those which are lengthy and extensive, being prudent in dealing with disputes and conflicts in order to preserve the atmosphere of the Quranic texts, rich in Quranic connotations, linking the Quran with everyday contemporary affairs, emphasis on faith ('aqidah) issues, defending the Quran from doubts and suspicions, and explaining the wisdom behind rulings. These methods in Hawwa's tafsir are not merely due to his understanding of Zilal al-Qur'an, also results from his interactions in the events and life experiences with the main objective of the Quran, as well as from his involvement activities in against the secular politics of Syria. Hawwa's involvement in Muslim Brotherhood and his early life in Islamic surrounding considered as the main influencing factor to his exegesis method and his view on current Muslim affairs.